The Recreational Activities and Their Influence on Learning Mathematics Based Students - Faraday Intriago Conforme, Diego; Vegas Melendez, Hilarion (International Journal of Psychosocial Rehabilitation, 2020)
The intention of this article is to provide a global perspective on the use of recreational resources and technological didactics for the teaching of mathematics at the level of higher education, through an analysis of specialized documentation. The benefit of this research work stems from the need to improve the teaching of mathematics by developing the interest of students through a kinesthetic playful approach, incorporating enjoyable, pleasant and didactic activities, helping students discover in an experiential way, new ways of learning and achieving the proposed objectives. The analysis and review of the documentation related to this topic are based on works concerning the incorporation of games for the teaching of mathematics. To obtain the results an instrument was applied where teachers and students intervene, highlighting that the teaching of mathematics for students is boring, tedious, complicated because teachers do not apply active methodologies that allow them to assimilate the contents and can achieve significant learning by improving your academic mathematical performance.